Aspect and pragmatics in Polish with a view to Sorbian - Karolina Zuchewicz (LingBaW)
In this paper, I discuss the meaning of the perfective aspect in Polish by taking a look at the so-called general-factual contexts, i.e., contexts that refer to completed events. Slavic languages rely on both perfective and imperfective aspect in such cases but differ concerning specific restrictions on aspect choice (Altshuler 2014; Dickey 2000; Gehrke 2022, 2023; Grønn 2004; Klimek-Jankowska 2020, 2022; Łaziński 2020; Mehlig 2011; Mueller-Reichau 2018; Wiemer 2001, 2008, among many others). Whereas speakers of East Slavic languages mostly choose the imperfective aspect in general-factual contexts, speakers of West Slavic languages face a stronger competition between imperfective and perfective forms. This paper highlights the role of pragmatics in aspect choice in general-factual contexts in Polish. It makes use of the notion of pragmatic contract (Israeli 1996 for Russian) and argues that, while the presence of a contract correlates with a preference for the perfective aspect, the absence of a contract triggers a preference for imperfective forms. These assumptions are verified with data from the Narodowy Korpus Języka Polskiego (Przepiórkowski et al. 2012). The paper further shows that the pragmatic contract does not influence aspectual distribution in Upper Sorbian, pointing to a difference in the aspectual systems of the two West Slavic languages and confirming the status of Polish as transitional between East and West Slavic.